Implementation of Sport Education Model (SEM) to Increase Learning Interest and Critical Reasoning Ability of Grade VI Elementary School Students in PJOK Subject in Pagedongan Sub-District - Sulistiono Sulistiono; Ristiana Dyah Purwandari (UM Purwokerto Press, 2025)
This research aims to determine the effect of learning videos on interest and learning outcomes for class VI SD Negeri 1 Pagedongan for the 2023/2024 academic year. This type of research is quasi-experimental research with The Posttest-Only Control-Group Design. Data on learning interest was collected using an assessment instrument in the form of a questionnaire and learning outcome data using a description test instrument. Data was analyzed using analysis assisted by SPSS 23 for Windows. The results of the research show that: First, there is a significant influence of Sport Education Model on the interest in learning PJOK of class VI students at SD Negeri 1 Pagedongan, Pagedongan District, Banjarnegara Regency for the 2023/2024 academic year. Second, there is a significant influence of Sport Education Model on PJOK learning outcomes for class VI students at SD Negeri 1 Pagedongan, Pagedongan District, Banjarnegara Regency for the 2023/2024 academic year. And third, there is a significant influence of Sport Education Model on interest and learning outcomes in PJOK in class VI students at SD Negeri 1 Pagedongan, Pagedongan District, Banjarnegara Regency for the 2023/2024 academic year.